High‐power‐factor electronic ballast zero voltage switching and low dv/dt with combination of charge pump and valley fill based on class DE. Issue 12 (1st December 2014) - Thongkullaphat, Sarayoot; Liutanakul, Pisit; Chunkag, Viboon
Abstract : In this study, for application of 36 W/220 Vrms /50 Hz fluorescent lamp, a high performance of high‐power‐factor and low line input current harmonics of electronic ballast is proposed. The proposed ballast has a structure based on a combination of charged pump and valley fill circuit. By adding paralleled capacitors to each power switch and setting the circuit parameters, operation modes of the inverter can be modified from single‐stage conventional class D to a class DE. Consequently, duty ratio can be reduced by up to 25% so that the voltage stress at power switch is lower when compared with the conventional class D inverter. Furthermore, switching power loss and d v /d t can also be reduced because of zero voltage switching condition. Details of design and circuit operation are described. The experimental results of prototype circuit, operated around 50 kHz of switching frequency at full power output, show that the proposed ballast has 94.48% of efficiency, 4.30% of THDi, 0.996 of input power factor and 1.38 of lamp current crest factor.